PERBEDAAN KEMAMPUAN MENGGAMBAR BERBASIS CAD SISWA SMK DENGAN MENGGUNAKAN JOBSHEET - 52-59 . Ikasiti Romadhuna (Universitas Negeri Padang, 2013)
The case of this study is what there are students capability in drawing of CAD-based between students who use jobsheet media with students who use konvensional media. The research is a experimental method with pre-experimental design in the static group comparison. The population in this study is all of students of class XI Teknik Gambar Bangunan SMK N 2 Solok which is amount 43 people. The analysis data was done thorugh : (1) Data description, (2) Pre-Analysis test, (3) Hypotesis test. From the analysis show that the result of study learning that using jobsheet media better then students that using conventional media. There is a big difference is student who are tought using jobsheet media more active and enthusiastic in drawing, than jobsheet taught using conventional media. Key words : menggambar berbasis cad, jobsheet, kemampuan siswa